Construction of big data open platform for telecom operators - Haifeng ZHANG; Zhao DONG; Juan LI; Lei QI; Huiqiong GU (Dianxin kexue)
Big data is accelerating the application across various industries,the opening of the data will help operators in the internal aggregation and sharing,and help to serve the ever-changing application scenarios,this is important for operators to develop new business.The background of combining big data with cloud computing was analyzed,overall architecture of big data platform for cloud computing was proposed,then the big data open platform implementation scheme was focused on,the platform planning and the problems to be solved in the project were carried out,and the reference for the related researchers were provided.